Impact of profit Accounting Processing on the National Economy (مجلة الواحات للبحوث والدراسات, 2025)
This research aims to study the Impact of accounting treatment of profits on the national economy, and this is based on the legal accounting and auditing methods used in the economic field, mainly represented in the correct way to calculate profits, and the results reveal a relationship between the concept of accounting treatment of profits and the national economy, as the analytical approach Through the study reveals the existence of a negative impact on the economy, if the method of calculating profits contrary to economic legislation, but if they are identical, this impact will be positive on investment and the national economy.  Keywords:Accounting, profit, Auditing, National economy, Economic legislation.